Efektifitas Pembelajaran Fikih dalam Peningkatan Kemampuan Praktik Ibadah Peserta Didik Kelas VII MTs DDI Padanglolo - Hanawiah hanawiah (Publikasi Indonesia, 2022)
Islam already has a reference or guideline in guiding humans. Therefore, the values ??of religious teachings originating from the word of God can be used to inspire the spirit of their faith so that self-control, self-actualization, self-inventory, and self-confidence can be developed. The effectiveness of Islamic jurisprudence in worship practices at Madrasah Tsanawiyah DDI Padanglolo, the purpose of the program is to provide students with the knowledge of ritual ablution and prayer procedures so that they can worship properly in accordance with Islamic law, which can be practiced and become a habit in the daily life of the students. This research is a type of quantitative research. Quantitative research methods could be interpreted as research methods based on the philosophy of positivism used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical with the aim of testing hypotheses has been established. The results of this study are expected to increase the contribution of discourse and insight in the field of Islamic religious education, increase research knowledge and student service activity on Islamic jurisprudence and learning effectiveness. With the existence of religious fiqh learning at Madrasah Tsanawiyah DDI Padanglolo, Pinrang Regency can improve the practice of praying for class VII students. So that it could be said that fiqh learning is very effective in improving the practice of praying for students at Madrasah Tsanawiyah DDI Padanglolo. The factors that affect the ability of students to pray are internal factors and external factors. These two factors have a big impact in developing the ability of student’s religious education.